Pendampingan Pengolahan dan Pengemasan Tanaman Obat Keluarga di Dusun Kemesu Kulon Progo Daerah Istimewa Yogyakarta: Assistance in Processing and Packaging of Family Medicinal Plants in Kemesu Kulon Progo, Yogyakarta Special Region - Gunawan, Barbara (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
The purpose of this service is to provide training and assistance on the processing and packaging of medicinal plants to develop an economically independent community. Business partners in this program Family Welfare Movement, Kemesu village, Kulon Progo Regency, Special Region of Yogyakarta. The problem faced by a partner is the lack of knowledge about how to process medicinal plants so that they can be of added value and can be sold so that they can increase income for the family. The method used to solve the problem is by Providing counseling about the use of medicinal plants, Providing training in the manufacture of herbal drink bag product, Providing training and assistance on how to pack herbal drink bag product, and providing training and assistance on how to marketing herbal drink bag product. The final results showed an increase in knowledge after being given education and training, namely the manufacture of herbal products to be packaged and branded, product marketing, obtaining PIRT from the Health Office of the Kulon Progo Regency until printed and distributed by the Family Medicinal Plant Guidebook.